Temporary shocks and unavoidable transitions to a high-unemployment regime - Wouter J. Den Haan (European Central Bank (ECB), 2003)
This paper develops a model with multiple steady states (low tax and unemployment rate versus high tax and unemployment rate) in which equilibrium selection is not conditioned on a sunspot variable. Instead, large enough shocks initiate unavoidable transitions from one regime to the other. The predictions of this paper are consistent with the persistent increase of European unemployment rates observed during the seventies. The explanation given is that even if the unemployment rate would decrease it can only do so gradually because of matching frictions which in turn implies that the tax burden remains high and job creation remains low making the return to a low unemployment rate impossible. The paper shows that in some cases transition to the low-unemployment regime is not possible when tax rates are adjusted each period to balance the budget even though this would be possible under an alternative policy with lower tax rates and (temporary) budget deficits.
Keywords: D50; C62; E24; E62; J64; 330; Fiscal Policy; Matching Model; Multiple Equilibria; Tax burden; Unemployment Benefits